Analyses of the associated technical and economic risks of the simple and intercooled Brayton helium recuperated gas turbine cycles for Generation IV nuclear power plants - Gad-Briggs, Arnold; Pilidis, Pericles; Nikolaidis, Theoklis (ASME, 2018)
The Simple Cycle Recuperated (SCR) and Intercooled Cycle Recuperated (ICR) are highly efficient Brayton helium gas turbine cycles, designed for the Gas-cooled Fast Reactor (GFR) and Very-High-Temperature Reactor (VHTR) Generation IV (Gen IV) Nuclear Power Plants (NPPs). This paper documents risk analyses which considers technical and economic aspects of the NPP. The sensitivity analyses are presented that interrogate the plant design, performance and operational schedule and range from component efficiencies, system pressure losses, operating at varied power output due to short term load-following or long term reduced power operations to prioritise other sources such as renewables. The sensitivities of the economic and construction schedule are also considered in terms of the discount rates, capital and operational costs and increased costs in Decontamination and Decommissioning (D&D) activity due to changes in the discount rates. This was made possible by using a tool designed for this study to demonstrate the effect on the ‘non-contingency’ baseline Levelised Unit Electricity Cost (LUEC) of both cycles. The SCR with a cycle efficiency of 50%, has a cheaper baseline LUEC of $58.41/MWh in comparison to the ICR (53% cycle efficiency), which has a LUEC of $58.70 /MWh. However, the cost of the technical and economic risks is cheaper for the ICR resulting in a final LUEC of $70.45/MWh (ICR) in comparison to the SCR ($71.62/MWh) for the year 2020 prices.
Keywords: Gen IV; Efficiency; Work; Cycle; Nuclear Power Plants; Performance; Simple; Intercooled; Levelised Unit Electric Cost